Aplicação de subdoses dos herbicidas glyphosate, 2,4-d e paraquat em algodoeiro - Melero, Mariana Moreira [UNESP] (2016)
The Brazil is among the largest producers of cotton. The objective of this study was to evaluate the effects of doses of application of glyphosate herbicide, 2,4-D and paraquat in cotton under field conditions. For all three crop years (2010/2011, 2011/2012 and 2013/2014), three essays have been installed and the experimental design was the randomized blocks, with 6 treatments and 4 repetitions, totaling 24 plots for each the tests. In the first experiment, the treatments were a combination of doses of glyphosate, as follows: 0.0 (control); 26.0; 52.0; 78.0; 104.0; and 130.0 g a.e. ha-1; in the second trial, the treatments consisted of the application of 2,4-D herbicide doses, as follows: 0.0 (control); 0.68; 1.36; 2.04; 2.72; and 3.40 g a.e. ha-1; And in the third test, the treatments were a combination of doses of the herbicide paraquat, as follows: 0.0 (control); 4.8; 9.6; 14.4; 19.6; and 24.0 g a.i. ha-1. The cotton productivity in core sub-dose increased to 52 g a.e glyphosate ha-1 in the year 2010/11, not being observed this effect in the year 2011/12 and for the year 2013/2014, an increase of production, but there was no statistical difference. In the second trial , there was no decrease in cotton productivity in seed in the three years of research and, the third test, productivity did not suffer application of interference in the first two years of study, for the third year, paraquat showed statistically significant results, the dosage being 24 g a.i.. ha-1 presented the highest increase in production compared to the control.